2020
DOI: 10.1038/s41467-020-14834-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural ensemble of a glutamate transporter homologue in lipid nanodisc environment

Abstract: Glutamate transporters are cation-coupled secondary active membrane transporters that clear the neurotransmitter L-glutamate from the synaptic cleft. These transporters are homotrimers, with each protomer functioning independently by an elevator-type mechanism, in which a mobile transport domain alternates between inward-and outward-oriented states. Using single-particle cryo-EM we have determined five structures of the glutamate transporter homologue Glt Tk , a Na + -L-aspartate symporter, embedded in lipid n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
112
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(123 citation statements)
references
References 57 publications
9
112
2
Order By: Relevance
“…In this so-called "unlocked" conformation, there was sufficient space for HP2 to open. More recent studies of ASCT2 and of an archaeal GltTk further showed that HP2 could open, suggesting that it serves as a gate in both the OFS and IFS (Garaeva et al, 2019;Arkhipova et al, 2020). Here, we report a series of Cryo-EM structures of GltPh reconstituted into nanodiscs in the IFS and OFS.…”
mentioning
confidence: 68%
“…In this so-called "unlocked" conformation, there was sufficient space for HP2 to open. More recent studies of ASCT2 and of an archaeal GltTk further showed that HP2 could open, suggesting that it serves as a gate in both the OFS and IFS (Garaeva et al, 2019;Arkhipova et al, 2020). Here, we report a series of Cryo-EM structures of GltPh reconstituted into nanodiscs in the IFS and OFS.…”
mentioning
confidence: 68%
“…These results suggest that in the absence of transmembrane electrochemical gradients and substrate, hEAAT3 g strongly favors the inward-facing conformation, similar to the archaeal homologue Glt Tk 34 . In this state, at least under our imaging conditions, the transporter has a remarkably low substrate affinity, perhaps in tens of mM.…”
Section: Resultsmentioning
confidence: 78%
“…of 1.3 Å, with the most significant conformational changes occurring in TM7 and HP2 (Figure 2e) . In further considering the coupling mechanism, we took advantage of the observations that the conformational changes underlying ion and substrate binding are confined to transport domains and similar in the outward- and inward-facing states of glutamate transporters 34,37,38 . We, therefore, compared the transport domains of IFS-Apo, IFS-Na + , and OFS-Asp to visualize structural events during binding.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray crystal structures and, more recently, single-particle cryo-electron microscopy (cryo-EM) structures of several members of the SLC1A family have revealed distinct conformations within the transport cycle. Structures of EAAT1 11 , neutral amino acid transporter 2 (ASCT2) [12][13][14] , and the archaeal homologs, GltPh 2, 15-22 and GltTk [23][24][25] have shown that SLC1A transporters share a similar trimeric structure in which each protomer, comprising a transport and a scaffold domain, can function independently [25][26][27] . EAATs utilize a twisting elevator mechanism of transport, in which the transport domain, containing the substrate and co-transport ion binding sites, shuttles across the membrane during transport while the scaffold domain makes inter-subunit contacts and remains anchored to the membrane 2,13 .…”
Section: Introductionmentioning
confidence: 99%